Improving the Metacognition Ability of Class VIII Middle School Students on the Use of Function Boards in Mathematics - Nugraha, Azi; Isulis Marissa, Erlinda (Journal Socio Humanities Review, 2022)
Metacognition is critical to achieving success in learning, so it is important to examine the activity and growth of metacognition to ensure effective teaching methods that enable students to utilize their information effectively while regulating their metacognitive processes. However, in reality, students' metacognitive capacity is still lacking. One important component to improve students' metacognition is their initial knowledge about the material being studied. Various ways are used to convey material, one of these ways is by using educational media. The board functions as a pedagogical tool in mathematics education, specifically designed to illustrate abstract understanding of relationships and functions to middle school students in grade 8. The research methodology used is quantitative research using Pretest-Posttest Control Group Design. This design involves two different groups or classes: the experimental class and the control class. The research focused on the population of class VIII students at SMP Negeri 1 Sumedang. The instrument used was a metacognitive ability test given to the experimental class after mathematics learning was completed, using a functional whiteboard. The data collection method used is a test approach. The data analysis techniques used include the use of the difference between two means test and the n-gain test to assess the amount of growth. These findings show a significant increase in the metacognitive abilities of students who were taught using a functional whiteboard, compared to those who were taught without using a functional whiteboard.